2022
DOI: 10.1039/d2nj00559j
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium-based ionic liquids with increasing alkyl chain length of cations decrease the stability and fibrillation propensity of lysozyme

Abstract: Ionic liquids (ILs) are neoteric solvents having a wide range of applications. Interaction of ILs with proteins alters their stability and self-aggregation. The present work analyses the effect of hydrophobic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
(105 reference statements)
2
7
0
Order By: Relevance
“…It is observed that lysozyme lost all the four disulfide bonds with the addition of 100‐fold excess of DTT (Figure S2). This DTT‐reduced unfolded form significantly lost its secondary structure and exposes its hydrophobic core as reported earlier [49,64] . This confirmation drives the protein to form fibrils rapidly via nucleation‐independent pathway through the interchain interactions of the exposed hydrophobic core [49,65] .…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…It is observed that lysozyme lost all the four disulfide bonds with the addition of 100‐fold excess of DTT (Figure S2). This DTT‐reduced unfolded form significantly lost its secondary structure and exposes its hydrophobic core as reported earlier [49,64] . This confirmation drives the protein to form fibrils rapidly via nucleation‐independent pathway through the interchain interactions of the exposed hydrophobic core [49,65] .…”
Section: Discussionsupporting
confidence: 70%
“…Such a switch in fibril formation mechanism is reported for lysozyme in the presence of imidazolium‐based ionic liquids [64] and for serum albumin in guanidinium chloride [84] . To analyze the overall effect of amino acids, irrespective whether they induce a lag phase, the apparent fibrillation time ( T app ) was calculated using equation 6 [64] . From this, Δ T app (= T app in individual amino acid − T app in buffer) was derived (Figure 12).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In sharp contrast, stabilization of proteins by artificial means is usually achieved by addition of large stoichiometric excess kosmotropic salts, 5 saccharides and related polyols, 6 polar amino acids, 7-10 polymers, 11-17 nanogels 18 and ionic liquids. [19][20][21] A common characteristic of these additives is that typically their high concentration (>100 mM for small molecules or 10 mg mL -1 for polymers) is required to achieve satisfactory results. In such cases, however, the high concentration of additives changes the general properties of the solution, including viscosity, ionic strength, refractive index and chemical compatibility.…”
mentioning
confidence: 99%